: Inggris - Munawarah; Nur Cahyati Ngaisah; Ikhsan (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Habituation activities are the beginning of the formation of children's character. Habituation activities are also the method of choice which is the school's flagship program in stimulating children's character development. The child's character is the attitude, behavior that is characteristic of himself, the character can change according to the stimulation given. The method of this research is to use a qualitative research method with a descriptive method, the research subjects in this study are students, the data analysis technique uses the Miles and Hiberman models where data analysis is carried out using an interactive method. Data collection techniques namely conducting observations, interviews and documentation. The results of this study indicate that the internalization of habituation activities is carried out in the following ways: 1. Daily habituation activities, 2. daily prayer habituation activities. 3. The habituation of reading hadiths, 4. The activity of memorizing the Koran (Juz 30).